Correlations between subdural empyema and paraclinical as well as clinical parameters amongst urban Malay paediatric patients - Mat Nayan, Saiful Azli; Abdullah, Mohd Shafie; Naing, Nyi Nyi; Mohd Haspani, Mohd Saffari; Md. Ralib@Md. Raghib, Ahmad Razali (Universiti Sains Malaysia, 2008)
Paediatric subdural empyema is frequently seen in developing Asean countries secondary to rinosinusogenic origins. A cross-sectional analysis on the surgical treatment of intracranial subdural empyema in Hospital Kuala Lumpur (HKL), a major referral center, was done in 2004. A total number of 44 children who fulfilled the inclusion criteria were included into this study. The methods of first surgery, volume of empyema on contrasted CT brain, improvement of neurological status, re-surgery, mortality and morbidity, as well as the demographic data such as age, gender, sex, duration of illness, clinical presentation, probable origin of empyema, cultures and follow-up were studied. Chi-square test was performed to determine the association between surgical methods and the survival of the patients, neurological improvement, clearance of empyema on CT brain, re-surgery and long morbidity among the survivors. If the 20% or more of the cells were having expected frequency less than five, then Fisher’s Exact test was applied. The level of significance was set at 0.05. SPSS version 12.0 was used for data entry and data analysis. There were 44 patients who were less than 18 years. Their mean age was 5.90 ± 6.01 years. There were 30 males (68.2%) and 14 females (31.8%) involved in the study. Malays were majority with 28 (63.6%) followed by Indian 8 (18.2%), Chinese 5 (11.4%) and others 3 (6.8%). The variables which were under interest were gender, race, headache, vomiting, seizures, sign of meningism, cranial nerve palsy, thickness site of abscess, first surgical treatment, improvement in neurological deficit, clearance of CT and whether re-surgery was necessary. All variables were found not to be associated with Henk W Mauser Score for PISDE grading. Comparison between this urban study and a rural setting study by the same corresponding author in the same period on subdural empyema was done. Common parameters were compared and it was found out that seizures were more prevalent in urban study where the patients are more than one year old (p=0.005). Mortality was much higher in urban study than the rural one (p=0.040). The larger proportion of urban group had volume of abscess less than or equal to 50 ml (p=< 0.001).